2021
DOI: 10.1111/1365-2656.13557
|View full text |Cite
|
Sign up to set email alerts
|

Natural and anthropogenic sources of habitat variation influence exploration behaviour, stress response, and brain morphology in a coastal fish

Abstract: Evolutionary ecology aims to better understand how ecologically important traits respond to environmental heterogeneity. Environments vary both naturally and as a result of human activities, and investigations that simultaneously consider how natural and human‐induced environmental variation affect diverse trait types grow increasingly important as human activities drive species endangerment. Here, we examined how habitat fragmentation and structural habitat complexity affect disparate trait types in Bahamas m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 133 publications
(154 reference statements)
0
9
0
Order By: Relevance
“…Given the amount of work pointing towards links between habitat features and brain evolution in fishes, it is somewhat surprising that there was no detectable correlation in our dataset. For example, effects of habitat complexity on brain size and/or organization have been shown for cichlids (Shumway, 2010), gobies (White & Brown, 2015), mosquito fish (Jenkins et al, 2021), salmon (Kihslinger & Nevitt, 2006), sunfish (Axelrod et al, 2018) and sticklebacks (Gonda et al, 2009). That being said, a previous analysis on a smaller dataset did not find evidence for an influence of brain size on invasion success in fishes (Drake, 2007), one of the key arguments for the ‘cognitive buffer hypothesis’ (Sol, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Given the amount of work pointing towards links between habitat features and brain evolution in fishes, it is somewhat surprising that there was no detectable correlation in our dataset. For example, effects of habitat complexity on brain size and/or organization have been shown for cichlids (Shumway, 2010), gobies (White & Brown, 2015), mosquito fish (Jenkins et al, 2021), salmon (Kihslinger & Nevitt, 2006), sunfish (Axelrod et al, 2018) and sticklebacks (Gonda et al, 2009). That being said, a previous analysis on a smaller dataset did not find evidence for an influence of brain size on invasion success in fishes (Drake, 2007), one of the key arguments for the ‘cognitive buffer hypothesis’ (Sol, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This pervasive ecosystem fragmentation has caused strong and consistent ecological changes in tidal creeks-for example, reduced tidal exchange, reduced species diversity, increased density of Gambusia, decreased density (or extirpation) of piscivorous fish (e.g., Layman et al, 2004;Valentine-Rose et al, 2007a, 2007b-and led to a number of phenotypic shifts in Bahamian mosquitofish (e.g., Giery et al, 2015;Heinen-Kay et al, 2014;Jenkins et al, 2021;Riesch et al, 2015), including dietary changes (Araújo et al, 2014;Langerhans et al, 2021). Prior work has characterized many of these tidal creeks regarding the population density of Gambusia and the density of predatory fish using visual surveys, and we aimed to use general linear models to test for associations between these variables and cannibalism in this study (N = 3,173 specimens from 24 fragmented and 22 unfragmented tidal creeks).…”
Section: Gambusia Hubbsi G Manni and G Sp From The Bahamasmentioning
confidence: 99%
“…Romero, 2004;Sapolsky et al, 2000) as shown in, e.g., fish prey living in high-predation localities (e.g. Archard et al, 2012;Brown et al, 2005;Fischer et al, 2014;Jenkins et al, 2021). Moreover, as the predation regimes in the blue holes have been relatively constant for thousands of years (Heinen-Kay & Langerhans, 2013;Langerhans et al, 2007;Martin et al, 2015;Riesch et al, 2013), we hypothesized that differences in stress reactivity would reflect evolutionary divergence rather than phenotypic plasticity.…”
Section: Introductionmentioning
confidence: 97%